Slab Upwarping of Twin-Block Slab Track on Subgrade–Bridge Transition Section: Parameter Study and Repair Method. Issue 1 (January 2014) - Ren, Juanjuan; Yang, Rongshan; Wang, Ping; Yong, Peng; Wen, Chao
This study is a preliminary analysis of the causes of upwarping of reinforced concrete slabs of a twin-block slab track, specifically on the subgrade–bridge transition section. The analysis considers the structural features and force characteristics of slab track on the basis of site investigations and numerical simulation, and a corresponding repair method is proposed. It is determined that the temperature and temperature gradient of the slab, the connection status between the slab and the hydraulically bonded layer (HBL), and the position of the terminal spine are the main factors that lead to the upwarping of the slab. Model tests on the force transmission parameters between slab and HBL are carried out to measure the adhesive strength of the cohesive contact and the friction coefficient for the frictional contact. The adhesive strength is found to range from 0.803 to 1.57 MPa. The actual friction coefficient with large dispersion varies significantly from 1.5 to 3.0 because of the influence of the strength of the material and the friction roughness. The analysis output shows that the upwarping of the slab decreases with the reduction of temperature and temperature gradient of the slab, but the upwarping increases with the decrease in adhesive strength and friction coefficient. Increasing the number of terminal spines with 4-m spacing, which is optimized after the spacing effect, contributes to the reduction of the slab upwarping. A reasonable layout scheme for anchor pins can significantly improve the integrity and stability of track structure affected by slab upwarping. From the output of the analysis, a repair method that involves setting additional anchor pins between the slab and HBL is thus recommended.